Optimal Control of a Class of Phase Change Processes with Terminal State Observation (Journal of Partial Differential Equations, 1993)
A class of optimal control problems for nonlinear evolutionary processes governed by two-phase Stefan problems is analyzed. The processes with terminal state observation are considered in the case of one space dimension. Approximate optimal solutions (controls, as well as the corresponding states and adjoint states), referring to the problems with time-averaged state observation are shown to converge to the appropriate solutions for the original problem.
Keywords: free boundary; optimal control; terminal observation; approximate solutions